A microbial driver of clay mineral weathering and bioavailable Fe source under low-temperature conditions - Jung, Jaewoo; Chung, Hyun Young; Ko, Youngtak; Moon, Inkyeong; Suh, Yeon Jee; Kim, Kitae (Frontiers in Microbiology, 2022)
Biotic and abiotic Fe(III) reduction of clay minerals under low temperature (0 °C and 4 °C, pH 6) was studied to evaluate the effects of bioalteration on soil properties including clay structure and elemental composition. The extent of Fe reduction in bioreduced samples (~3.8 % at 4 °C and ~3.1 % at 0 °C) was lower than abiotic reduction (~7.6 %) using dithionite as a strong reductant. However, variations in the illite crystallinity value of bioreduced samples (°Δ2θ = 0.580–0.625) were greater than those of abiotic reduced samples (°Δ2θ = 0.580–0.601), indicating that modification of crystal structure is unlikely to have occurred in abiotic reduction. Moreover, precipitation of secondary-phase minerals such as vivianite (Fe2+3(PO4)2·8H2O) and nano-sized biogenic silica were shown as evidence of reductive dissolution of Fe-bearing minerals that is observed only in a bioreduced setting. Our observation of a previously undescribed microbe–mineral interaction at low temperature suggests a significant implication for the microbially mediated mineral alteration in Arctic permafrost, deep sea sediments, and glaciated systems resulting in the release of bioavailable Fe with an impact on low-temperature biogeochemical cycles.